Pengaruh Gaya Hidup Dan Harga Terhadap Keputusan Pembelian Produk Thrifting (Studi Kasus Mahasiswa Institut STIAMI Fakultas Administrasi Tahun Akademik 2024/2025) - Badriawan, Anike Suci; Muthi'ah, Firyal Luthfi (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aims to examine and analyze the influence of lifestyle and price on purchasing decisions of thrifting products among students of the Faculty of Administrative Sciences, Institut Ilmu Sosial dan Manajemen STIAMI, during the 2024/2025 academic year. Thrifting products, as a fashion alternative offering affordability and unique aesthetic value, are increasingly favored by university students. The research employs a quantitative method with a descriptive and associative approach. The sampling technique used is purposive sampling, with a total of 100 active students as respondents. Data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression analysis, t-test, and F-test with the assistance of SPSS version 27. The findings indicate that both lifestyle and price have a significant influence on purchasing decisions, both partially and simultaneously. Among the two variables, lifestyle shows a more dominant influence compared to price. These findings suggest that trends, personal preferences, and lifestyle awareness are the primary factors driving students’ decisions to purchase thrifting products.